2022
DOI: 10.3390/app12199933
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development of Heavy Atom-Free Triplet Photosensitizers for Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) is an attractive method for cancer treatment. Triplet photosensitizers (PSs) are critical for this method; upon photoexcitation, efficient intersystem crossing (ISC) occurs for triplet PSs, the triplet-excited state of the triplet PSs is populated, then via intermolecular triplet energy transfer, the O2, in triplet-spin multiplicity at ground state, is sensitized to the singlet-excited state, i.e., singlet oxygen (1O2) is produced. This strong reactive oxygen species (ROS) will oxidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 134 publications
0
21
0
Order By: Relevance
“…Previously, NDIs with amino substitution, which show strong absorption of visible light and intense emission in the red spectral range, were studied mainly for fluorescence and redox properties. It is important to mention that red-light-absorbing compounds are beneficial for applications, i.e., PDT. ,, Moreover, it was reported that amino substitution of the NDI core shifts the absorption from the UV range of the NDI chromophore to the visible light region or even beyond 600 nm, and by introducing the stable radicals, the ISC quantum yield was enhanced up to 74% . Recently, NDI-derived compact electron donor–acceptor dyads and triads were reported, in which NDI acts as an electron acceptor and anthracene serves as an electron donor.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, NDIs with amino substitution, which show strong absorption of visible light and intense emission in the red spectral range, were studied mainly for fluorescence and redox properties. It is important to mention that red-light-absorbing compounds are beneficial for applications, i.e., PDT. ,, Moreover, it was reported that amino substitution of the NDI core shifts the absorption from the UV range of the NDI chromophore to the visible light region or even beyond 600 nm, and by introducing the stable radicals, the ISC quantum yield was enhanced up to 74% . Recently, NDI-derived compact electron donor–acceptor dyads and triads were reported, in which NDI acts as an electron acceptor and anthracene serves as an electron donor.…”
Section: Introductionmentioning
confidence: 99%
“…Among various PSs, heavy-atom-free PSs have the advantages of a low toxicity, low synthesis cost, and long triplet state lifetime. 2,[15][16][17] Traditional triplet PSs invoke the heavy atom effect 3,18 or n-p* 2 p-p* transitions to promote ISC; 19,20 however, they are associated with the limitations of difficult synthesis, short triplet-state lifetimes, 21 limited molecular structures, 15 and so forth. In this regard, triplet PSs based on heavy atom-free molecular structure motifs, such as the spin-orbit charge transfer ISC (SOCT-ISC) mechanism, have attracted much attention owing to their simple molecular structures, feasible derivatization, and efficient ISC.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,14,15 Several protocols have been developed to enhance the ISC in heavy atom-free organic molecules, including the use of the orthogonality of the two chromophore planes (or the HOMO and LUMO) and energy matching conditions for the singlet and triplet manifolds. 1,14,15 Carbonyl compounds, such as benzophenone and biacetyls, 7,10,16 with n → π* transitions, are representative examples of these kinds of triplet PSs. Moreover, molecular structures with a twisted π-conjugation framework can increase the SOC matrix elements, thus enhancing the ISC.…”
mentioning
confidence: 99%
“…Thus, other approaches, including heavy atom-free compounds with a reasonable compromise between the SOC strength and the lifetime of the T 1 state, are strongly desired. However, the design of a new heavy atom-free PS is still a challenge in photochemistry. ,,, …”
mentioning
confidence: 99%
See 1 more Smart Citation